HISTOMORPHOMETRIC EVALUATION OF POLYP AND PAPILLOMA TISSUES IN THE HUMAN URINARY BLADDER - Shodiev Ulmas Mustafoevich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This study presents a morphometric and histological analysis of urinary bladder polyps and papillomas. Specimens collected from cystoscopic biopsies were studied to determine  their  cellular  composition,  epithelial-stromal  relationships, and structural features  using  hematoxylin-eosin  staining  and  morphometric  imaging  software. Results  indicate  key  differences  in  epithelial  thickness,  vascularization,  and inflammatory infiltration between polyps and papillomas. These findings support the importance of detailed tissue analysis in the differential diagnosis of bladder lesions.